Lighting conditions in selected low-income Filipino households - Dela Cruz, Janette Suerte M.
This descriptive research aimed to study the lighting conditions in selected low-income Filipino households. Interviews and observations were conducted to gather the necessary data. To facilitate the data gathering, the following instruments were used: a digital camera, an observation checklist, a drawing pad and a tape measure. The community where the study was conducted was selected through purposive sampling and the eight (8) respondents/households were chosen based on their availability and willingness to participate. The gathered data were tabulated and were subjected to ranking and averaging. Results showed that the respondents were quite satisfied with the lighting conditions in their houses even if empirical data revealed that these did not meet the requirements of good lighting. Out of the three conditions of good lighting which include visual comfort, biological needs, and energy conservation, the households only addressed energy conservation. Biological needs and visual comfort were compromised as a result. Low electrical consumption translated into low monthly bills was the underlying factor in the prevailing lighting practices of the eight (8)households. Among such practices include the sharing of light among the different areas in the house which often resulted to poor illumination or insufficient lighting in some portions of the areas. Minimal use of the lighting fixtures and a significant dependence on natural lighting or light coming from the adjacent areas were also observed. In the living area where most of the activities happened, most of the respondents used inappropriate lighting fixture with low wattages which were not suitable to the size of the area, much more to the numerous activities being accommodated there.